Exploiting the innate behaviour of common carp, Cyprinus carpio, to limit invasion and spawning in wetlands of the River Murray, Australia. (28th October 2016) - Conallin, A. J.; Smith, B. B.; Thwaites, L. A.; Walker, K. F.; Gillanders, B. M.
Abstract: Common carp, Cyprinus carpio L., a destructive invasive pest of the Murray–Darling Basin, Australia, move from rivers into wetlands to spawn, making them vulnerable to trapping, but traps may also capture and affect access for native species. This study trialled a trap designed to separate carp from native fish entering wetlands by exploiting their different jumping and pushing behaviours. Trials were conducted at a flow‐through wetland on the River Murray, South Australia, from June to October 2008. No carp approached the wetland inlet, but many ( n = 3736) were sampled at the outlet, most by the trap ( n = 2530), but there was some avoidance. Ninety‐two percent of trapped carp were successfully isolated by jumping or pushing. Separation was most efficient (and avoidance least) when carp were ready to spawn (water temperature >16 °C). The outlet design substantially reduced wetland carp invasion, but more trials are needed to assess the pushing ability of native fish, to deter entry by turtles, and with alternatives for wetland inlets.